2017
DOI: 10.4067/s0719-38902017005000201
|View full text |Cite
|
Sign up to set email alerts
|

TRITICALE (x Triticosecale Wittmack): RENDIMIENTO Y SUS COMPONENTES EN UN AMBIENTE SEMIÁRIDO DE LA ARGENTINA

Abstract: RESUMENEl rendimiento de grano por unidad de superficie y algunos de sus componentes de 18 líneas experimentales de triticales graníferos y tres cultivares doble propósito, se evaluaron durante 2009 a 2015 en Santa Rosa (36°37′ S, 64°17′ W), Provincia de La Pampa, Argentina, sobre un Paleoustol petrocálcico en condiciones naturales. La siembra se realizó bajo un diseño en bloques completos al azar con tres repeticiones y parcelas estándar. Se realizó el análisis de varianza (ANOVA) conjunto para los distintos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Within the varieties, the values presented a similar trend, although variety 7 of late habit was the one that presented the highest average value of 54 seeds per ear, which is why this is directly linked to the number of spikelets per spike, according to Velasco et al (2020) who obtained higher results fluctuating between 73 and 59 (NSS). However, Paccapelo et al (2017) reported values that ranged between 39 and 28 seeds per spike. According to the results reported by Beji (2016), for the number of seeds per spike, it reports values of 34 to 20 seeds per spike in triticale.…”
Section: Resultsmentioning
confidence: 99%
“…Within the varieties, the values presented a similar trend, although variety 7 of late habit was the one that presented the highest average value of 54 seeds per ear, which is why this is directly linked to the number of spikelets per spike, according to Velasco et al (2020) who obtained higher results fluctuating between 73 and 59 (NSS). However, Paccapelo et al (2017) reported values that ranged between 39 and 28 seeds per spike. According to the results reported by Beji (2016), for the number of seeds per spike, it reports values of 34 to 20 seeds per spike in triticale.…”
Section: Resultsmentioning
confidence: 99%
“…Triticale (X Triticosecale Wittmack) is a species that competes with oats (Avena sativa L.), wheat (Triticum aestivum L.), rye (Secale cereale L.), and barley (Hordeum vulgare L.) for winter forage production, especially in areas where oats are displaced by frost (Paccapelo et al, 2017). This cereal was developed to combine the grain quality of wheat with the rusticity of rye, receiving the majority of the breeding work from both parents, granting its agronomic aptitudes with good forage and grain yields, excellent nutritional qualities, and wide adaptability to diverse geographic environments (Oliete et al, 2010;Kweon et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Argentina is an important winter wheat and triticale producer in the world (Wrigley et al, 2016). This country produces around 16.5 million tons of wheat per year in an area of ~5.4 million hectares and ~122 tons of triticale per year in ~45 thousand hectares (Paccapelo et al, 2017;SIIA, 2016). Only ~6 million tons of wheat is for domestic consumption while the rest is exported, whereas the production of triticale is entirely for domestic supply (FAOSTAT, 2015).…”
Section: Introductionmentioning
confidence: 99%